A thermally/chemically robust and easily regenerable anilato-based ultramicroporous 3D MOF for CO2 uptake and separation. Issue 44 (8th November 2021) - Monni, Noemi; Andres-Garcia, Eduardo; Caamaño, Katia; García-López, Víctor; Clemente-Juan, Juan Modesto; Giménez-Marqués, Mónica; Oggianu, Mariangela; Cadoni, Enzo; Mínguez Espallargas, Guillermo; Clemente-León, Miguel; Mercuri, Maria Laura; Coronado, Eugenio
Abstract : A novel anilato-based 3D ultramicroporous MOF is reported, displaying a significant balance of high CO2 separation from CO2 :N2 and CO2 :CH4 gas mixtures, high thermal stability and high regenerability, a challenge in the separation technology industry. Abstract : The combination of a properly designed organic linker, 3, 6- N -ditriazolyl-2, 5-dihydroxy-1, 4-benzoquinone (trz2 An), with Co II ions results in a novel 3D ultramicroporous MOF with high CO2 uptake capacity and separation efficiency, with particular attention to CO2 /N2 and CO2 /CH4 gas mixtures. This material consists of 1D chains of octahedrally coordinated Co II ions linked through anilato ligands at the equatorial positions and triazole substituents from two neighbouring chains at the two axial positions. This leads to a 3D microporous structure with voids with an affinity for CO2 molecules and channels that enable the selective entry of CO2 but not of molecules with larger kinetic diameters such as N2 or CH4 . Adsorption studies revealed that (i) the MOF presents a remarkable carbon dioxide uptake, above 20% in weight; (ii) CO2 adsorptive separation is successfully performed in CO2 :N2 and CO2 :CH4 gas mixtures, exhibiting high selectivity in a large operation range; (iii) regeneration is easily achieved under mild conditions.